Exploring the impact of sense of work gain on kindergarten teachers’ work performance: the mediating role of organizational commitment and the moderating influence of supportive leadership - Wenxiu Shi; Yile Zheng (Frontiers in Psychology)
IntroductionThe concept of sense of work gain encapsulates the profound psychological gratification and forward-looking aspirations that arise when an individual’s dedicated efforts at work are met with equitable material and spiritual compensation. Despite a wealth of research on its correlation with job satisfaction and innovative behaviors among educators, the underlying mechanisms linking sense of work gain to job performance remain understudied. This study introduces a nuanced moderated mediation framework to elucidate the pathways through which sense of work gain influences the job performance of teachers, spotlighting the pivotal role of organizational commitment and the nuanced impact of supportive leadership.MethodsWith a focus on the kindergarten teaching workforce, an extensive survey was administered to 1,081 educators across Shaanxi and Gansu provinces in China. Subsequent hypothesis testing was performed using statistical tools SPSS 27.0 and AMOS 24.0.ResultsThe research results indicated that sense of work gain had a significant positive predictive effect on the job performance of kindergarten teachers. Organizational commitment played a mediating role between sense of work gain and the job performance of kindergarten teachers. Supportive leadership not only positively moderated the relationship between sense of work gain and the job performance of kindergarten teachers but also positively moderated the relationships between sense of work gain and organizational commitment, as well as between organizational commitment and job performance.DiscussionThese findings revealed a significant positive effect of job fulfillment on the work performance of kindergarten teachers and elucidated the mediating effect of organizational commitment as well as the positive moderating role of supportive leadership in this process. These discoveries emphasized the importance of enhancing teachers’ job fulfillment, strengthening organizational commitment, and cultivating a supportive leadership style for optimizing the work performance of kindergarten teachers, providing education administrators with effective strategies for improving teachers’ working environment and enhancing teaching quality.